Crossing Lines, Crossing Borders: Filipino Call Center Agents as Virtual Migrants - Nava, Ericka Lynne (Archīum Ateneo, 2019)
In the course of call center agents’ transnational service work, agents’ subjectivities are formed under the split conditions of inhabiting America and the Philippines. Other researchers have called this experience virtual migration. The study analyzes and examines the ways that virtual migration affects Filipino call center agents’ formulation, understanding, and expression of their national and cultural identity. Findings reveal that agents’ cultivation and performance of an Americanized identity can Americanize agents to a degree that is not commonly found in Filipinos who have not physically migrated to Americanized spaces. The experience of being diasporic is thus extended to call center agents who do not leave the homeland. Nevertheless, the virtuality of their migration means that agents are reintegrated back into the web of Filipino family life and community, albeit at limited amounts, during their off days. Additionally, it must be noted that cultural hybridity is not a foregone outcome. Rather, call center agents exercise their agency in choosing whether or not to adopt or reject the new cultural elements that they inhabit for their work. In this process, the specter of the Philippines’ colonial past interjects: Filipinos’ regard for anything American may limit their desire to resist cultural hybridization. Hybridization, or lack thereof, is thus the result of a negotiated and dynamic process that results from the interplay of the past and the present, of global forces and local actors, playing out through both material and virtual space. The result is a spectrum of hybridizations of national and cultural identity that range from complete hybridity to an impermanent pseudohybridity.